Extracorporeal life support in pregnant and postpartum women with COVID-19-related acute respiratory distress syndrome. Issue 5 (May 2023) - El Banayosy, Ahmed M; El Banayosy, Aly; Smith, Jennifer G; Brewer, Joseph M; Mihu, Mircea R; Swant, Laura V; Schoaps, Robert S; Sharif, Ammar; Benson, Clayne; Maybauer, Marc O
Objective: Extracorporeal membrane oxygenation (ECMO) is an intervention used for patients with acute respiratory distress syndrome (ARDS) from COVID-19 who have failed conventional ventilatory strategies. Very few studies have given insight into the outcomes of pregnant and postpartum patients requiring ECMO support. Methods: Single center, retrospective, observational study of female pregnant and postpartum patients suffering COVID-19 ARDS and requiring ECMO. Results: Eight SARS-CoV-2 positive patients were identified. The average age was 31 ± 4 years, with Body Mass Indices (BMI) and SOFA scores ranging between 32–49 and 8–11, respectively. Two patients were pregnant at the time of ECMO initiation, two were peripartum, and four were postpartum. Five patients (63%) had bleeding, and one patient had a hysterectomy. Seven patients (88%) were supported by V-V ECMO and one with V-A ECMO. Patients had between one and three circuit exchanges due to oxygenator failure or clots in the circuit. All patients were in ICU between 7 and 74 days, with hospital length of stay between 8 and 81 days. All patients were weaned off ECMO and were successfully discharged from the hospital. All newborns were born via cesarean section, and all survived to discharge. Conclusion: Our study shows a 100% neonatal and maternal survival rate demonstrating that ECMO in this patient population is safe. These patients should be transferred to experienced high-volume ECMO centers with the ability to perform emergent cesarean sections. ECMO should be considered a life-saving therapy for pregnant women with severe COVID-19 with an overall excellent maternal and neonatal survival rate.